Inorganic salt phase change cold storage material and preparation method thereof
By using a variety of inorganic salts and modified nucleating agents and other materials, combined with microcapsule encapsulation technology, the problem of poor circulation stability of inorganic salt phase change materials during thermal cycles is solved, and high thermal conductivity and long-term stable phase change performance are achieved.
Patent Information
- Application Number
- CN202411601247.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
AI Technical Summary
Inorganic salt/hydrated salt phase change materials have phase stratification and supercooling after multiple melt-solidation thermal cycles, with poor circulation stability and deterioration of phase change performance.
A variety of inorganic salts, modified nucleating agents, thickening agents, ultrapure water and microcapsules modified doping stable shell materials are used to form modified phase change materials through specific preparation methods. The method includes modifying nanosilver particles on the surface of expanded graphite, increasing thermal conductivity, and improving the cyclic stability of the material through microcapsule encapsulation technology.
It significantly improves the thermal conductivity and cyclic stability of inorganic salt phase change materials, reduces the supercooling degree, avoids phase separation, extends the service life of the material, and does not affect its latent heat of phase change.
Smart Images

Figure BDA0005128368180000111 
Figure BDA0005128368180000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phase change energy storage materials, in particular to an inorganic salt phase change cold storage material and a preparation method thereof. Background Art
[0002] Phase change materials / phase change energy storage materials (PCM) belong to the category of energy materials. In a broad sense, it refers to materials that can be used to store energy by absorbing (releasing) a large amount of heat energy when the physical state changes. In a narrow sense, it refers to those materials that have high energy storage density, stable performance, suitable phase change temperature and excellent cost performance during solid-liquid phase change, and can be used in phase change energy storage technology. Obviously, phase change energy storage (heat and cold) technology is a high-tech technology based on phase change energy storage materials. Because it has a large energy storage density and the output temperature and energy are quite stable, it has advantages that are difficult to match with sensible heat storage. At present, phase change energy storage technology can be used as the basis for the development of industrial energy-saving systems and high-tech products to meet people's requirements for special performance and cost of systems and products.
[0003] Shape-fixed phase change energy storage materials can maintain their original shape (solid state) before and after the phase change. They can be divided into solid-fixed phase change energy storage materials and solid-liquid shape-fixed phase change energy storage materials. The unique properties of shape-fixed phase change materials give them broad application prospects, and they are used as thermal insulation wall materials in the field of building energy conservation. Solid-solid phase change materials mainly include high-density polyethylene, layered calcium titanium and inorganic salts. Solid-liquid shape-fixed phase change energy storage materials are actually a type of composite phase change materials, which are mainly composed of two components: one is the working substance; the other is the carrier matrix. The working substance uses its solid-liquid phase change to store energy, which can be various solid-liquid phase change materials, such as paraffin, stearic acid, hydrated salt, inorganic salt, etc. The carrier matrix is mainly used to maintain the non-flowability and processability of the material. Various shape-fixed phase change energy storage materials have been developed, such as paraffin / high-density polyethylene qualitative phase change materials, cross-linked shape-fixed phase change energy storage materials with different gel rates, and new inorganic salt / ceramic-based ultra-microstructure shape-fixed energy storage materials.
[0004] The research on phase change materials is becoming more and more extensive, and some phase change materials have been commercialized, but people have not made any breakthrough progress in the research on the stability and reliability of high latent heat phase change materials. Except for metals, all phase change materials have the problem of low thermal conductivity and poor heat transfer performance, which obviously affects the speed of energy storage and release. Therefore, how to enhance heat transfer in material technology is still an issue that needs to be strengthened in phase change energy storage technology.
[0005] Inorganic salt / hydrated salt phase change materials have high latent heat density and a wide range of melting points, making them promising phase change materials. However, during the research and experimental process, after multiple melting-solidification thermal cycles, the mixture will experience phase stratification and supercooling, poor cycle stability, and deterioration of phase change performance, which has long been the main problem that needs to be solved in inorganic salt / hydrated salt latent heat storage technology. Summary of the invention
[0006] The object of the present invention is to provide an inorganic salt phase change cold storage material and a preparation method thereof, so as to solve the problems raised in the background technology.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] An inorganic salt phase change cold storage material is made from the following raw materials in parts by weight:
[0009] 32-48 parts of various inorganic salts;
[0010] 2.8-3.4 parts of modified nucleating agent;
[0011] Thickener 78-86 parts;
[0012] Ultrapure water 64-96 parts;
[0013] 280-350 parts of microcapsule modified and doped stable shell material.
[0014] Furthermore, the plurality of inorganic salts are two or three of magnesium chloride, ammonium aluminum sulfate, potassium aluminum sulfate, magnesium nitrate and aluminum nitrate.
[0015] Furthermore, the molar ratio of the various salts of the plurality of inorganic salts is (0.7-0.8):(0.2-0.3) or (0.6-0.67):(0.2-0.3):(0.03-0.2).
[0016] Further, the preparation steps of the modified nucleating agent are as follows:
[0017] A1, immersing expanded graphite and dopamine hydrochloride in tris(hydroxymethylaminomethane) hydrochloride buffer and stirring at room temperature for 24 h to obtain the EG@PDA initial framework;
[0018] The pH of the tris hydrochloride buffer is 7.8-8.4;
[0019] It should be noted that expanded graphite (EG) is a loose and porous worm-like substance with a large number of network-like microporous structures. Its large specific surface area, high surface activity and a large number of unique network-like microporous structures inside make it have good adsorption, coating and thermal conductivity. Dopamine hydrochloride undergoes oxidation self-polymerization to form polydopamine and adheres and fills on the surface and voids of expanded graphite. The prepared EG@PDA initial skeleton has a large number of activation sites. With the help of capillary action and van der Waals force, the saturated liquid eutectic hydrate salt is adsorbed in the internal pores, which reduces the leakage of the phase change material while reducing the supercooling of the phase change material. It has obvious mesoporous confinement effect in the phase change process, effectively inhibits phase separation, improves the cycle stability of long-term use, and does not affect the phase change latent heat of the eutectic inorganic salt.
[0020] A2. Add ammonia water to the AgNO3 solution to prepare a silver-ammonia solution, add the EG@PDA initial framework and polyvinyl pyrrolidone to the silver-ammonia solution, stir magnetically for 1 hour, add the glucose solution to the mixed solution, stir in a water bath at 40°C for 12 hours, centrifuge, wash, and dry to obtain a modified nucleating agent.
[0021] It should be noted that the nanosilver particles are loaded and modified onto the initial skeleton of EG@PDA. The nanosilver particles have high thermal conductivity, which can improve the thermal conductivity of the phase change material as a whole, and have antibacterial properties, which can prevent the phase change material from mold to a certain extent in a non-cold storage and non-clean environment.
[0022] Furthermore, the concentration of the AgNO3 solution is 0.01-0.04 mol / L; the mass fraction of the ammonia water is 0.5-2%; and the concentration of the glucose solution is 0.02-0.08 mol / L.
[0023] Furthermore, the dosage ratio of the expanded graphite, dopamine hydrochloride and tris(hydroxymethylaminomethane) hydrochloride buffer solution is (0.08-0.1) g:(0.34-0.4) g:(12-15) mL; the dosage ratio of the AgNO3 solution, ammonia water, EG@PDA initial skeleton, polyvinyl pyrrolidone and glucose solution is 3 mL:10 mL:(0.03-0.05) g:3.2 mg:3 mL.
[0024] Furthermore, the thickener is one or more of borax, sodium alginate, sodium carboxymethyl cellulose, bentonite, starch, guar gum, pectin, and animal glue.
[0025] It should be noted that adding a suitable thickener to the hydrated salt energy storage material can enhance the viscosity of the solution, so that the solid particles in the liquid can be more evenly distributed in the solution without settling to the bottom, thus overcoming the crystal-liquid separation (phase separation).
[0026] Furthermore, the microcapsule modified doped stable shell material is formed by in-situ polymerization and encapsulation of a microcapsule modified doped stable shell material preparatory liquid, and the preparation steps of the microcapsule modified doped stable shell material preparatory liquid are as follows:
[0027] Acetone, lipophilic emulsifier, auxiliary emulsifier, methyl methacrylate monomer and stabilizer are placed in a reaction kettle, and the temperature of the reaction kettle is controlled at 40° C. to obtain a microcapsule modified doped stable shell material;
[0028] It should be noted that the microcapsule modified doped stable shell material is a layer of stable polymer film coated on the surface of the solid-liquid phase change material particles. By encapsulating the core material, the hydrated salt phase change main material is isolated from the outside world during the microcapsule formation process, and energy is exchanged with the outside world to achieve energy storage and release, forming an inorganic salt phase change cold storage material with a core-shell structure. During the phase change process, the phase change material as the inner core undergoes a solid-liquid phase transition, and the outer polymer film remains in a solid state, thereby improving the overall cycle stability of the phase change material. The various salt phase change main materials are confined in a certain area so that they cannot agglomerate, thereby achieving the purpose of improving the dispersion performance of the inorganic salt; at the same time, the microcapsule modified doped stable shell material provides a relatively large nucleation specific surface area for the various salt phase change core materials, accelerates the crystallization of the core material, and reduces the supercooling of the core material.
[0029] It needs to be reiterated that, on the one hand, the encapsulation rate of the monomer polymerization method is higher, the emission of harmful residues is lower, it is friendly to industrial production, and it is not easy to cause core leakage or implosion due to poor encapsulation rate. In addition, the modified and doped stable shell material of microcapsules can form larger-sized inorganic salt phase change cold storage material particles. Smaller particle sizes are prone to thermodynamically unstable emulsions and larger polymerization heat, which cannot be quickly dispersed and cause microcapsules to burst, and incomplete coatings are generated on the surface of the phase change main material, resulting in core leakage, uneven wall thickness, and reduced thermal enthalpy.
[0030] The stabilizer is hexagonal boron nitride nanosheets.
[0031] It should be noted that hexagonal boron nitride nanosheets as high thermal conductivity nanoparticles are interspersed in the microcapsule modified doped stable shell material, giving the inorganic salt phase change cold storage material a certain compressive strength and corrosion resistance.
[0032] Furthermore, the usage ratio of the acetone, lipophilic emulsifier, auxiliary emulsifier, methyl methacrylate monomer and stabilizer is (3.8-5.5) mL: (4-6) g: 0.5 g: (5.7-8.3) mL: (3-5) mg.
[0033] A preparation method of an inorganic salt phase change cold storage material comprises the following steps:
[0034] S1. Heat a plurality of inorganic salts in a water bath until they are melted, sequentially mix ultrapure water, a thickener, and a nucleating agent into the melted plurality of inorganic salts, and fully homogenize them by magnetic stirring, dry them at a temperature of 90° C. for 30 minutes, take them out of the oven and cool them at room temperature, remove the inorganic salts remaining on the surface, and obtain a phase change main core material;
[0035] S2, dispersing the phase change main core material in the microcapsule modified doped stable shell material preparatory liquid at a rate of 400r / min, slowly adding the initiator, homogenizing at a speed of 800r / min at 40°C for 1.5h to form a viscous emulsion, gradually heating from 40°C to 60°C, stabilizing the temperature at intervals of 5°C for 10min, stirring continuously for 30min and then standing until no precipitation occurs, taking the precipitate, filtering, washing, drying, and distilling it through a rotary evaporator to obtain an inorganic salt phase change cold storage material;
[0036] The usage ratio of the phase change main core material, the microcapsule modified doping stable shell material and the initiator is (9-13) g: (15-22) mL: (0.04-0.06) g.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. Dopamine hydrochloride undergoes oxidation and self-polymerization to form polydopamine, which adheres to and fills the surface and gaps of expanded graphite. It has a large number of activation sites, and the high thermal conductivity nanosilver particles are loaded and modified on it, which improves the thermal conductivity of the phase change material as a whole, reduces leakage, reduces supercooling, improves cycle stability, does not affect the latent heat of phase change, and the antibacterial properties of the modified material can also prevent the phase change material from getting moldy. Thickeners can make the solid particles in the liquid more evenly distributed in the solution without settling to the bottom, overcoming crystal-liquid separation.
[0039] 2. A layer of stable polymer film is coated on the surface of the phase change main material, and the phase change main material is isolated from the outside world through encapsulation, and energy is exchanged with the outside world to achieve energy storage and release, thereby improving the overall cycle stability of the phase change material. The various salt phase change main materials are confined in a certain area so that they cannot agglomerate, thereby achieving the purpose of improving the dispersion performance of inorganic salts; at the same time, the microcapsule modified doped stable shell material provides a relatively large nucleation specific surface area for the various salt phase change core materials, accelerates the crystallization of the core material, and reduces the supercooling of the core material.
[0040] 3. The modified and doped microcapsules have a high encapsulation rate and low harmful residue emissions. They are friendly to industrial production and are not prone to core leakage or implosion caused by poor encapsulation rates. They can form large-sized, uniformly thick, and complete inorganic salt phase change cold storage material particles. They are thermodynamically stable, have low polymerization heat, can be dispersed quickly, will not cause microcapsules to burst, and avoid leakage of the phase change main material and reduction of thermal enthalpy. Hexagonal boron nitride nanosheets, as high thermal conductivity stabilizers, can give inorganic salt phase change cold storage materials certain compressive strength and corrosion resistance. DETAILED DESCRIPTION
[0041] The following will be combined with embodiments to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The preparation steps of the modified nucleating agent are as follows:
[0043] A1, 0.1g expanded graphite and 0.4g dopamine hydrochloride were immersed in 15mL tris(hydroxymethyl)aminomethane hydrochloride) buffer with a pH of 8, and stirred at room temperature for 24h to obtain the EG@PDA initial framework;
[0044] A2. Add 10 mL of 1% ammonia water to 3 mL of 0.02 mol / L AgNO3 solution to prepare a silver ammonia solution. Add 0.05 g of EG@PDA initial skeleton and 3.2 mg of polyvinyl pyrrolidone to the silver ammonia solution. After magnetic stirring for 1 h, add 3 mL of 0.04 mol / L glucose solution to the mixed solution. Stir in a water bath at 40 ° C for 12 h, centrifuge, wash, and dry to obtain a modified nucleating agent.
[0045] The steps for preparing the modified and doped stable shell material of microcapsules are as follows:
[0046] 5 mL of acetone, 5 g of sorbitan monooleate, 0.5 g of polysorbate, 7.6 mL of methyl methacrylate monomer and 4.32 mg of hexagonal boron nitride nanosheets were placed in a reactor, and the temperature of the reactor was controlled at 40° C. to obtain a microcapsule modified doped stable shell material preparatory liquid. The microcapsule modified doped stable shell material was formed by in-situ polymerization and encapsulation of the microcapsule modified doped stable shell material preparatory liquid.
[0047] Example 1
[0048] An inorganic salt phase change cold storage material is made from the following raw materials in parts by weight:
[0049] 30 parts of ammonium aluminum sulfate;
[0050] 10 parts of potassium aluminum sulfate;
[0051] 3.1 parts of modified nucleating agent;
[0052] 54.5 parts of sodium alginate;
[0053] 27.5 parts of sodium carboxymethyl cellulose
[0054] Ultrapure water 80 parts;
[0055] 315 parts of microcapsule modified and doped stable shell material.
[0056] A preparation method of an inorganic salt phase change cold storage material comprises the following steps:
[0057] S1. Heat ammonium aluminum sulfate and potassium aluminum sulfate in a water bath until they are melted, mix ultrapure water, thickener, and nucleating agent into the molten salt in turn, and fully homogenize by magnetic stirring, dry at 90° C. for 30 min, take out from the oven and cool at room temperature, remove the salt remaining on the surface, and obtain the phase change main core material;
[0058] S2. Disperse 12g of the phase change main core material in 18.5mL of the microcapsule modified doped stable shell material preparatory solution at a rate of 400r / min, slowly add 0.05g of ammonium persulfate initiator, homogenize at 800r / min at 40°C for 1.5h to form a viscous emulsion, gradually heat from 40°C to 60°C, stabilize the temperature at an interval of 5°C for 10min, continue stirring for 30min and let it stand until no more precipitation occurs, take the precipitate, filter, wash, dry, and distill it through a rotary evaporator to obtain an inorganic salt phase change cold storage material.
[0059] Example 2
[0060] An inorganic salt phase change cold storage material is made from the following raw materials in parts by weight:
[0061] 24 parts of ammonium aluminum sulfate;
[0062] 8 parts of potassium aluminum sulfate;
[0063] 2.8 parts of modified nucleating agent;
[0064] 52 parts of sodium alginate;
[0065] 26 parts of sodium carboxymethyl cellulose
[0066] Ultrapure water 64 parts;
[0067] 280 parts of microcapsule modified and doped stable shell material.
[0068] A preparation method of an inorganic salt phase change cold storage material comprises the following steps:
[0069] S1. Heat ammonium aluminum sulfate and potassium aluminum sulfate in a water bath until they are melted, mix ultrapure water, thickener, and nucleating agent into the molten salt in turn, and fully homogenize by magnetic stirring, dry at 90° C. for 30 min, take out from the oven and cool at room temperature, remove the salt remaining on the surface, and obtain the phase change main core material;
[0070] S2. Disperse 12g of the phase change main core material in 18.5mL of the microcapsule modified doped stable shell material preparatory solution at a rate of 400r / min, slowly add 0.05g of ammonium persulfate initiator, homogenize at 800r / min at 40°C for 1.5h to form a viscous emulsion, gradually heat from 40°C to 60°C, stabilize the temperature at an interval of 5°C for 10min, continue stirring for 30min and let it stand until no more precipitation occurs, take the precipitate, filter, wash, dry, and distill it through a rotary evaporator to obtain an inorganic salt phase change cold storage material.
[0071] Example 3
[0072] An inorganic salt phase change cold storage material is made from the following raw materials in parts by weight:
[0073] 36 parts of ammonium aluminum sulfate;
[0074] 12 parts of potassium aluminum sulfate;
[0075] 3.4 parts of modified nucleating agent;
[0076] Sodium alginate 57 parts;
[0077] 29 parts of sodium carboxymethyl cellulose
[0078] Ultrapure water 96 parts;
[0079] 350 parts of microcapsule modified and doped stable shell material.
[0080] A preparation method of an inorganic salt phase change cold storage material comprises the following steps:
[0081] S1. Heat ammonium aluminum sulfate and potassium aluminum sulfate in a water bath until they are melted, mix ultrapure water, thickener, and nucleating agent into the molten salt in turn, and fully homogenize by magnetic stirring, dry at 90° C. for 30 min, take out from the oven and cool at room temperature, remove the salt remaining on the surface, and obtain the phase change main core material;
[0082] S2. Disperse 12g of the phase change main core material in 18.5mL of the microcapsule modified doped stable shell material preparatory solution at a rate of 400r / min, slowly add 0.05g of ammonium persulfate initiator, homogenize at 800r / min at 40°C for 1.5h to form a viscous emulsion, gradually heat from 40°C to 60°C, stabilize the temperature at an interval of 5°C for 10min, continue stirring for 30min and let it stand until no more precipitation occurs, take the precipitate, filter, wash, dry, and distill it through a rotary evaporator to obtain an inorganic salt phase change cold storage material.
[0083] Comparative Example 1
[0084] An inorganic salt phase change cold storage material is made from the following raw materials in parts by weight:
[0085] 30 parts of ammonium aluminum sulfate;
[0086] 10 parts of potassium aluminum sulfate;
[0087] 3.1 parts of expanded graphite;
[0088] 54.5 parts of sodium alginate;
[0089] 27.5 parts of sodium carboxymethyl cellulose
[0090] Ultrapure water 80 parts;
[0091] 315 parts of microcapsule modified and doped stable shell material.
[0092] A preparation method of an inorganic salt phase change cold storage material comprises the following steps:
[0093] S1. Heat ammonium aluminum sulfate and potassium aluminum sulfate in a water bath until they are melted, mix ultrapure water, thickener, and nucleating agent into the molten salt in turn, and fully homogenize by magnetic stirring, dry at 90° C. for 30 min, take out from the oven and cool at room temperature, remove the salt remaining on the surface, and obtain the phase change main core material;
[0094] S2. Disperse 12g of the phase change main core material in 18.5mL of the microcapsule modified doped stable shell material preparatory solution at a rate of 400r / min, slowly add 0.05g of ammonium persulfate initiator, homogenize at 800r / min at 40°C for 1.5h to form a viscous emulsion, gradually heat from 40°C to 60°C, stabilize the temperature at an interval of 5°C for 10min, continue stirring for 30min and let it stand until no more precipitation occurs, take the precipitate, filter, wash, dry, and distill it through a rotary evaporator to obtain an inorganic salt phase change cold storage material.
[0095] The difference between this comparative example and Example 1 is that no modified nucleating agent is added, but unmodified expanded graphite is added as the nucleating agent.
[0096] Comparative Example 2
[0097] An inorganic salt phase change cold storage material is made from the following raw materials in parts by weight:
[0098] 30 parts of ammonium aluminum sulfate;
[0099] 10 parts of potassium aluminum sulfate;
[0100] 54.5 parts of sodium alginate;
[0101] 27.5 parts of sodium carboxymethyl cellulose
[0102] Ultrapure water 80 parts;
[0103] 315 parts of microcapsule modified and doped stable shell material.
[0104] A preparation method of an inorganic salt phase change cold storage material comprises the following steps:
[0105] S1. Heat ammonium aluminum sulfate and potassium aluminum sulfate in a water bath until they are melted, mix ultrapure water, thickener, and nucleating agent into the molten salt in turn, and fully homogenize by magnetic stirring, dry at 90° C. for 30 min, take out from the oven and cool at room temperature, remove the salt remaining on the surface, and obtain the phase change main core material;
[0106] S2. Disperse 12g of the phase change main core material in 18.5mL of the microcapsule modified doped stable shell material preparatory solution at a rate of 400r / min, slowly add 0.05g of ammonium persulfate initiator, homogenize at 800r / min at 40°C for 1.5h to form a viscous emulsion, gradually heat from 40°C to 60°C, stabilize the temperature at an interval of 5°C for 10min, continue stirring for 30min and let it stand until no more precipitation occurs, take the precipitate, filter, wash, dry, and distill it through a rotary evaporator to obtain an inorganic salt phase change cold storage material.
[0107] The difference between this comparative example and Example 1 is that no modified nucleating agent is added.
[0108] Comparative Example 3
[0109] An inorganic salt phase change cold storage material is made from the following raw materials in parts by weight:
[0110] 30 parts of ammonium aluminum sulfate;
[0111] 10 parts of potassium aluminum sulfate;
[0112] 3.1 parts of modified nucleating agent;
[0113] 54.5 parts of sodium alginate;
[0114] 27.5 parts of sodium carboxymethyl cellulose
[0115] Ultrapure water 80 parts;
[0116] 315 parts of microcapsule modified and doped stable shell material.
[0117] A preparation method of an inorganic salt phase change cold storage material comprises the following steps:
[0118] Ammonium aluminum sulfate and potassium aluminum sulfate are heated in a water bath until they are melted, ultrapure water, thickener and nucleating agent are mixed into the molten salt in turn, and fully homogenized by magnetic stirring, and dried at 90°C for 30 minutes. The material is taken out of the oven and cooled at room temperature to remove the salt remaining on the surface, thereby obtaining an inorganic salt phase change cold storage material.
[0119] The difference between this comparative example and Example 1 is that the microencapsulation step of S2 is omitted.
[0120] 1. Testing
[0121] The probe of the hot plate thermal constant analyzer is placed between two phase change cold storage materials of the same specifications to measure the thermal conductivity of the inorganic salt phase change cold storage material.
[0122] The phase change latent heat, phase change temperature, supercooling and thermal cycle stability (200 times) of the inorganic salt phase change cold storage material were measured by differential scanning calorimetry. The inorganic salt phase change cold storage materials of Examples 1-3 and Comparative Examples 1-3 were placed in a differential scanning calorimeter, cooled to -35°C at a temperature change rate of 20°C / min, then heated to 35°C, and then kept at a constant temperature for 5 minutes, and then cooled to -35°C at a temperature reduction rate of 5°C / min. After maintaining the temperature for 5 minutes, the temperature was increased to 35°C at a temperature increase rate of 5°C / min.
[0123] The test results are shown in Table 1.
[0124] 2. Results Summary
[0125]
[0126]
[0127] Table 1
[0128] 3. Conclusion
[0129] 1. Compared with comparative examples 1-2, the thermal conductivity of embodiments 1-3 is higher; the thermal conductivity of comparative example 3 is the highest.
[0130] 2. Compared with Comparative Examples 1-3, the phase change latent heat of Examples 1-3 is higher.
[0131] 3. Compared with comparative example 1-2, the supercooling degree of embodiment 1-3 is smaller, and the supercooling degree of comparative example 3 is maintained at the same level as that of embodiment 1-3.
[0132] 4. Compared with comparative examples 1-3, the cycle stability of embodiments 1-3 is better, among which the cycle stability of the comparative example is the worst.
[0133] 5. In summary, the silver ion-modified EG@PDA modified nucleating agent plays a major role in improving thermal conductivity, phase change latent heat and cyclic stability and reducing supercooling; the modified nucleating agent and microcapsule modified doped stable shell material have no effect on the phase change temperature.
[0134] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0135] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
Claims
1. An inorganic salt phase change cold storage material, characterized in that: Made from the following raw materials in parts by weight: 32-48 parts of various inorganic salts; 2.8-3.4 parts of modified nucleating agent; Thickener 78-86 parts; Ultrapure water 64-96 parts; 280-350 parts of microcapsule modified and doped stable shell material.
2. The inorganic salt phase change cold storage material according to claim 1, characterized in that: The plurality of inorganic salts are two or three of magnesium chloride, ammonium aluminum sulfate, potassium aluminum sulfate, magnesium nitrate and aluminum nitrate.
3. The inorganic salt phase change cold storage material according to claim 1, characterized in that: The molar ratio of various salts of the plurality of inorganic salts is (0.7-0.8):(0.2-0.3) or (0.6-0.67):(0.2-0.3):(0.03-0.2).
4. The inorganic salt phase change cold storage material according to claim 1, characterized in that: The modified nucleating agent preparation steps are as follows: A1, immersing expanded graphite and dopamine hydrochloride in tris(hydroxymethylaminomethane) hydrochloride buffer and stirring at room temperature for 24 h to obtain the EG@PDA initial framework; The pH of the Tris hydrochloride buffer is 7.8-8.4; A2. Add ammonia water to the AgNO3 solution to prepare a silver-ammonia solution, add the EG@PDA initial framework and polyvinyl pyrrolidone to the silver-ammonia solution, stir magnetically for 1 hour, add the glucose solution to the mixed solution, stir in a water bath at 40°C for 12 hours, centrifuge, wash, and dry to obtain a modified nucleating agent.
5. The inorganic salt phase change cold storage material according to claim 1, characterized in that: The concentration of the AgNO3 solution is 0.01-0.04 mol / L; the mass fraction of the ammonia water is 0.5-2%; and the concentration of the glucose solution is 0.02-0.08 mol / L.
6. The inorganic salt phase change cold storage material according to claim 1, characterized in that: The usage ratio of the expanded graphite, dopamine hydrochloride and tris(hydroxymethylaminomethane) hydrochloride buffer solution is (0.08-0.1) g:(0.34-0.4) g:(12-15) mL; the usage ratio of the AgNO3 solution, ammonia water, the EG@PDA initial skeleton, polyvinyl pyrrolidone and glucose solution is 3 mL:10 mL:(0.03-0.05) g:3.2 mg:3 mL.
7. The inorganic salt phase change cold storage material according to claim 1, characterized in that: The thickener is one or more of borax, sodium alginate, sodium carboxymethyl cellulose, bentonite, starch, guar gum, pectin and animal glue.
8. The inorganic salt phase change cold storage material according to claim 1, characterized in that: The microcapsule modified doped stable shell material is formed by in-situ polymerization and encapsulation of a microcapsule modified doped stable shell material preparatory liquid. The preparation steps of the microcapsule modified doped stable shell material preparatory liquid are as follows: Acetone, lipophilic emulsifier, auxiliary emulsifier, methyl methacrylate monomer and stabilizer are placed in a reaction kettle, and the temperature of the reaction kettle is controlled at 40° C. to obtain a microcapsule modified doped stable shell material; The stabilizer is hexagonal boron nitride nanosheets.
9. The inorganic salt phase change cold storage material according to claim 1, characterized in that: The dosage ratio of the acetone, lipophilic emulsifier, auxiliary emulsifier, methyl methacrylate monomer and stabilizer is (3.8-5.5) mL: (4-6) g: 0.5 g: (5.7-8.3) mL: (3-5) mg.
10. The method for preparing the inorganic salt phase change cold storage material according to any one of claims 1 to 9, characterized in that: The specific steps are as follows: S1. Heat a plurality of inorganic salts in a water bath until they are melted, sequentially mix ultrapure water, a thickener, and a nucleating agent into the melted plurality of inorganic salts, and fully homogenize them by magnetic stirring, dry them at a temperature of 90° C. for 30 minutes, take them out of the oven and cool them at room temperature, remove the inorganic salts remaining on the surface, and obtain a phase change main core material; S2, dispersing the phase change main core material in the microcapsule modified doped stable shell material preparatory liquid at a rate of 400r / min, slowly adding the initiator, homogenizing at a speed of 800r / min at 40°C for 1.5h to form a viscous emulsion, gradually heating from 40°C to 60°C, stabilizing the temperature at intervals of 5°C for 10min, stirring continuously for 30min and then standing until no precipitation occurs, taking the precipitate, filtering, washing, drying, and distilling it through a rotary evaporator to obtain an inorganic salt phase change cold storage material; The usage ratio of the phase change main core material, the microcapsule modified doping stable shell material and the initiator is (9-13) g: (15-22) mL: (0.04-0.06) g.